Biodiesel Production Using Hydrodynamic Cavitation Phenomena - Chanphavong, Lemthong; Chanthaboune, Vongsavanh; Phonhalath, Keophousone (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study presents biodiesel production assisted by hydrodynamic cavitation process. Hydrodynamic cavitating flow test rig was fabricated for a lab-scale of 12 liters per batch using single and multiple hole orifice plates. High pressure multi-stage pump was used for generating circular fluid flow from a store rage tank passing through orifice plate before entering back to storage tank. Diameter of orifice hole was varied from 4, 5, and 6 mm for single hole orifice plate while 2 mm for multiple hole orifice pate (12 holes). Fresh vegetable oil was used as feedstock for transesterification reaction with methanol and potassium hydroxide based on molecular ratio of 6:1 and 1% by weight, respectively. Reaction time was a constant at 25 minutes. Result shown that, for single hole orifice plate case, decrease in hole diameter results in increasing in the inlet pressure, which provokes a biodiesel generation ratio increased. The multiple hole orifice provides a higher biodiesel generation ratio compared with the single hole case. This can be explained by that when the inlet pressure increased results in higher pressure loss which directly supported stronger cavitation flow. Similarly, the multiple hole orifice has a larger perimeter, which resulted in higher shear flow compared with the single hole one. Shear flows are directly linked to the stronger cavitating flow, which supported a higher biodiesel generation ratio.